Crystallography, in Silico Studies, and In Vitro Antifungal Studies of 2,4,5 Trisubstituted 1,2,3-Triazole Analogues - Katharigatta N. Venugopala; Mohammed A. Khedr; Yarabahally R. Girish; Subhrajyoti Bhandary; Deepak Chopra; Mohamed A. Morsy; Bandar E. Aldhubiab; Pran Kishore Deb; Mahesh Attimarad; Anroop B. Nair; Nagaraja Sreeharsha; Rashmi V; et al. (MDPI AG, 2020)
A series of 2,4,5 trisubstituted-1,2,3-triazole analogues have been screened for their antifungal activity against five fungal strains, Candida parapsilosis, Candida albicans, Candida tropicalis, Aspergillus niger, and Trichophyton rubrum, via a 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) microdilution assay. Compounds GKV10, GKV11, and GKV15 emerged as promising antifungal agents against all the fungal strains used in the current study. One of the highly active antifungal compounds, GKV10, was selected for a single-crystal X-ray diffraction analysis to unequivocally establish its molecular structure, conformation, and to understand the presence of different intermolecular interactions in its crystal lattice. A cooperative synergy of the C-H···O, C-H···N, C-H···S, C-H···π, and π···π intermolecular interactions was present in the crystal structure, which contributed towards the overall stabilization of the lattice. A molecular docking study was conducted for all the test compounds against Candida albicans lanosterol-14α-demethylase (pdb = 5 tzl). The binding stability of the highly promising antifungal test compound, GKV15, from the series was then evaluated by molecular dynamics studies.